Management of orthopedic oncology patients during coronavirus pandemic - Şahbat, Yavuz (J Surg Oncol, 2020)
The new measures implemented in hospitals also altered the operation of orthopedics and traumatology departments. The main purpose of this article is to discuss how orthopedic oncology clinics should be organized during the pandemic and to present the process management scheme for patients requiring orthopedic surgery, including trauma surgery, from diagnosis to treatment, together with our experiences. Instead of thinking about the global emergence of the epidemic, it is time to act decisively. At first glance, the coronavirus disease 2019 (COVID‐19) pandemic and orthopedics may seem to be unrelated disciplines, but the provision of healthcare services to patients who require them proves that these two fields are parts of the same whole. Our experiences in treating neutropenic, lymphocytopenic, and chemotherapy patients seem to have proven beneficial during this process. We operated on 10 biopsy patients, 15 primary bone sarcomas, 9 soft tissue sarcomas, and 82 trauma patients within this time frame. Only three patients were suspected to have COVID‐19 before admission. The early identification, strict isolation, and effective treatment of these patients prevented any nosocomial infections and disease‐related comorbidities. This success is the result of the multidisciplinary cooperation of the Ministry of Health, our hospital, and our clinic.